2006
DOI: 10.1080/13697130600727107
|View full text |Cite
|
Sign up to set email alerts
|

No differences in performance on test of working memory and executive functioning between healthy elderly postmenopausal women using or not using hormone therapy

Abstract: There was no relationship between neuropsychological performance, age of initiation of HT, or duration of HT use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 63 publications
0
14
0
1
Order By: Relevance
“…However, estrogen treatment in the perimenopausal period did not enhance memory (LeBlanc et al, 2007). In older post-mensopausal women, some studies show that estrogen use enhances performance on tests of verbal (Kampen and Sherwin, 1994) and visual or spatial memory (Duka et al, 2000;Smith et al, 2001); however, several others do not (File et al, 2002;Grigorova and Sherwin, 2006;Polo-Kantola et al, 1998;Schiff et al, 2005). Finally, there are no other studies to date that examine hormone effects on memory for emotional stimuli, particularly for images in the IAPS.…”
Section: Discussionmentioning
confidence: 92%
“…However, estrogen treatment in the perimenopausal period did not enhance memory (LeBlanc et al, 2007). In older post-mensopausal women, some studies show that estrogen use enhances performance on tests of verbal (Kampen and Sherwin, 1994) and visual or spatial memory (Duka et al, 2000;Smith et al, 2001); however, several others do not (File et al, 2002;Grigorova and Sherwin, 2006;Polo-Kantola et al, 1998;Schiff et al, 2005). Finally, there are no other studies to date that examine hormone effects on memory for emotional stimuli, particularly for images in the IAPS.…”
Section: Discussionmentioning
confidence: 92%
“…[266] recently provided evidence for executive dysfunction in untreated menopausal women, as women with hormone replacement therapy (HRT) outperformed women without HRT on tests requiring directed attention, inhibition of inappropriate responses, and cognitive set switching. A number of other studies have also provided evidence that estrogen enhances prefrontal cognitive processes such as working memory and attention [267][268][269][270][271][272][273][274], although there are dissenting reports [275]. For instance, a recent study by Joffe et.…”
Section: The Hippocampus and Prefrontal Cortex As Important Sites Of mentioning
confidence: 99%
“…Although some studies have reported that treatment with estrogen and progestin improves spatial and verbal memory [10, 25], other studies, including the Women’s Health Initiative (WHI) Memory Study and WHI Study of Cognitive Aging, report little or no benefit of estrogen plus progestin therapy on measures of both global cognitive function and specific memory abilities [23, 33, 34, 40]. These inconsistencies highlight the need to more clearly understand how estrogens and progestins (e.g., progesterone) influence cognitive function.…”
Section: Introductionmentioning
confidence: 99%